2017
DOI: 10.1177/2473011417s000011
|View full text |Cite
|
Sign up to set email alerts
|

FAAM ADL Scores Correlate with PROMIS Physical Function, Pain Interference, and Depression Outcomes

Abstract: Category: Midfoot/Forefoot Introduction/Purpose: Legacy patient-reported outcome instruments like the FAAM Activities of Daily Living (ADL) quantify patient disability but are often limited by responder burden and incomplete questionnaires. The Patient-Reported Outcome Measurement Information System (PROMIS) overcomes such obstacles through computer-adaptive technology to collect data on various health domains including Physical Function (PF), Pain Interference (PI), and Depression. Few reports, though, have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…34 It has shown good correlation with PROMIS instruments. 38,39,47 Initial validation of the FAAM Sports showed that its subscale was more responsive to change at 4 weeks than a general measure of physical function, 35 and generally responsive to change at 6 months. 21 Further validation studies are needed to assess the responsiveness of the PROMIS instruments and FAAM Sports within specific clinical populations and contexts.…”
mentioning
confidence: 99%
“…34 It has shown good correlation with PROMIS instruments. 38,39,47 Initial validation of the FAAM Sports showed that its subscale was more responsive to change at 4 weeks than a general measure of physical function, 35 and generally responsive to change at 6 months. 21 Further validation studies are needed to assess the responsiveness of the PROMIS instruments and FAAM Sports within specific clinical populations and contexts.…”
mentioning
confidence: 99%